1st International Conference on Biomedical Sciences, Dow University of Health Sciences, Karachi Pakistan - Zeba Haque; Farina Hanif; Muhammad Owais; Sonia Siddiqui (Journal of the Pakistan Medical Association, 2023)
Institute of Biomedical Sciences (IBMS) at Dow University of Health Sciences (DUHS), organised a two day’s conference on Biomedical Sciences. IBMS being the part of one of the largest public sector health universities of Pakistan, is now transforming the research trends to be effectively translated at the community level. Currently with a strong PhD faculty line in basic and clinical sciences, DUHS has a significant contribution in research output of the country. The scientific data however represents a small population per scientific study and the generalization of results may not be inferred. It must be extended through translational research for effectiveness. The conference was planned with a theme to bridge the gap between basic and translational research. The two day’s conference conducted in second week of March 2023 at Dow International Medical College Ojha Campus DUHS was able to attract more than 300 participants. The scientific sessions encompassed a vast variety of health issues and their proposed solutions including neurosciences, virtual biopsies, metabolomics, medical writings and incorporation of engineering and artificial intelligence to facilitate detection and prognosis of disease. The conference was able to conclude that the multidisciplinary research studies with collaboration of two or more institutes/organizations are the need of time. Young researchers need an effective platform to showcase their research and make collaborations. Moreover, the incorporation of artificial intelligence would enhance patient care within health systems. Keywords: Biomedical Sciences, basic research, Translational research, IBMS, DUHS.